2011
DOI: 10.1021/jp111275a
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle−Reactive Oxygen Species Interactions: Application of a Charging−Discharging Model

Abstract: The silver-nanoparticle-catalyzed decomposition of hydrogen peroxide (H2O2) in pH 9.5 bicarbonate buffer is investigated here with attention given to (i) the mechanism of decomposition, (ii) the role of superoxide in mediating silver nanoparticle re-formation, and (iii) the effect of nanoparticle size on decomposition rate. Silver nanoparticles (AgNPs) of average size between 25.0 and 69.4 nm were synthesized via the reduction of Ag+ [the dominant Ag(I) species present] by photochemically produced superoxide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 47 publications
(97 reference statements)
7
142
3
Order By: Relevance
“…Most of the Gram-negative organisms, including E. coli, possess an extra outermost layer made up of lipopolysaccharide and thus may restrict the damage to cell membrane of organisms (Wagh et al 2013). The antibacterial action of Au@ZnO nanostructures can be explained in the light of following four most common reported mechanisms: (1) the uptake of free Ag ions followed by the disruption of ATP production and DNA replication (Chernousova and Epple 2013), (2) the charging-discharging model for superoxide-mediated generation of reactive oxygen species (ROS) (He et al 2011), (3) the Ag NPs and Ag ions generation of ROS (Xu et al 2012), and (4) the Ag nanoparticles direct damage to the cell membranes (Gholap et al 2013;Panmand et al 2014). In our previous study (Patil et al 2015;Patil et al 2014), we have shown that ZnO nanostructures act on microbial cells by generating ROS on cellular membrane, which virtually oxidizes every cellular components and thus ruptures the cell wall.…”
Section: Antibacterial Activity Of Au@znomentioning
confidence: 99%
“…Most of the Gram-negative organisms, including E. coli, possess an extra outermost layer made up of lipopolysaccharide and thus may restrict the damage to cell membrane of organisms (Wagh et al 2013). The antibacterial action of Au@ZnO nanostructures can be explained in the light of following four most common reported mechanisms: (1) the uptake of free Ag ions followed by the disruption of ATP production and DNA replication (Chernousova and Epple 2013), (2) the charging-discharging model for superoxide-mediated generation of reactive oxygen species (ROS) (He et al 2011), (3) the Ag NPs and Ag ions generation of ROS (Xu et al 2012), and (4) the Ag nanoparticles direct damage to the cell membranes (Gholap et al 2013;Panmand et al 2014). In our previous study (Patil et al 2015;Patil et al 2014), we have shown that ZnO nanostructures act on microbial cells by generating ROS on cellular membrane, which virtually oxidizes every cellular components and thus ruptures the cell wall.…”
Section: Antibacterial Activity Of Au@znomentioning
confidence: 99%
“…The fluorescence of the sample was measured in a Cary Eclipse spectrophotometer using settings described previously [28,29]. For H 2 O 2 quantification, a calibration curve encompassing H 2 O 2 concentrations over the range of 75-600 nM was obtained.…”
Section: Determination Of H 2 Omentioning
confidence: 99%
“…Discharged nanoparticles (NPs) find their way into the soils during their manufacturing, transportation, application, and disposal (Pachapur et al, 2016), and soils and aquifers act as primary filter systems to remove particulate materials from percolating water and protect water resources (Kasel et al, 2013a;Liang et al, 2013a). Many previous studies have shown the negative effects of AgNPs on human health and the environment (e.g., He et al, 2011;Carbone et al, 2014). Hence, a detailed understanding of the processes governing the transport and retention of AgNPs in soil is required to accurately assess the fate and distribution of AgNPs and to design effective strategies for reducing their toxicity in the environment.…”
Section: Introductionmentioning
confidence: 99%